Characterization of peroxiredoxin from Neocaridina denticulata sinensis and its antioxidant and DNA protection activity analysis. Issue 127 (August 2022) - Zhang, Ruirui; Wang, Ying; Xu, Ce; Chen, Fei; Yu, Qili; Sun, Yuying; Zhang, Jiquan
Abstract: Peroxiredoxin (Prx) is an antioxidant protein that widely exists in various organisms. To further investigate the role of Prx in the antioxidant and immune responses of Neocaridina denticulata sinensis, the full-length cDNA sequence of a Prx gene ( Nd-Prx ) from N. denticulata sinensis was obtained. The open reading frame (ORF) of Nd-Prx is 597 bp and encodes 198 amino acids. Amino acid similarity alignment showed that Nd-Prx contained a conserved sequence region "FYPLDFTFVCPTEI". qRT-PCR assay showed that Nd-Prx was expressed in all tested tissues and its expression was highest in the ovary. Nd-Prx was most highly expressed at 36 h after copper stimulation. Nd-Prx expression levels in hepatopancreas were significantly upregulated after Vibrio parahaemolyticus challenge (P < 0.05). In addition, the recombinant Nd-Prx was prepared and its enzyme activity was most stable at 70 °C with pH of 6.0. The antioxidant activity and DNA protection of recombinant Nd-Prx was also demonstrated. In summary, this study investigated the role of Prx in antioxidant and immune responses of N. denticulata sinensis, which might provide a foundation for further exploring Prx in immune system of crustaceans and for the application in disease control. Graphical abstract: Image 1 Highlights: Nd-Prx gene was cloned and its recombinant protein was prepared to analyze its enzymatic activity. Nd-Prx was expressed in all tested tissues. Expression of Nd-Prx was elevated under copper exposure or V. parahaemolyticus challenge. The recombinant Nd-Prx exhibited high reducibility.